A W‐band long‐slot array antenna with two‐dimensional beam‐scanning capability - Tianye Ma; Kai‐Da Xu; Ye Deng; Jinping Zhang; Hongbin Sun (IET Microwaves, Antennas & Propagation, 2024)
Abstract A low‐cost W‐band leaky‐wave antenna with two‐dimensional scanning capability is presented. By using the low‐loss transversal long‐slot array structure with a single‐layer parabolic reflector, the antenna realizes a passband from 85 to 102.8 GHz with Voltage Standing Wave Ratio <2. This antenna has a backward radiation direction, which changes with frequency in one dimension, and with the feeding wave front direction in the other dimension. The maximum sidelobe is measured to be −14.2 dB, 5 dB lower compared to the previous‐published longitudinal long‐slot array. A low‐cost, low‐loss, low‐profile design is provided for W‐band 2‐D beam scanning, with backward scanning capability, which is easy to fabricate and could be used for high‐solution sensing and point‐to‐point communications.